A Conceptual Framework for Assessment Literacy: Opportunities for Physical Education Teacher Education. Issue 4 (2nd October 2018) - Starck, Jenna R.; Richards, K. Andrew R.; O'Neil, Kason
ABSTRACT: Although more nuanced understandings of assessment have been proposed in the physical education literature, assessment practices remain relatively underdeveloped, and when used, tend to focus on traditional, summative evaluations of learning. However, physical education teacher education programs can be used as an intervention to help pre-service teachers develop assessment knowledge and skill. Toward this end, the purpose of this article is to propose an evidence-based framework for helping pre-service teachers develop assessment literacy that is rooted in occupational socialization theory. The framework provides a four-phase approach to integrating assessment into teacher education, and includes suggestions for how physical education teacher educators can progressively help build pre-service teachers' assessment knowledge in line with the focus given to instruction and planning. These suggestions acknowledge the technical and sociocultural aspects of learning to use assessment. Implications are discussed along with the need to help graduating pre-service teachers transfer lessons learned into the workplace.